THE EFFECT OF DIGITAL TECHNOLOGY ON OPERATIONAL PERFORMANCE IN THE FOOD AND BEVERAGE INDUSTRY (FMCG) MEDIATED BY DIGITAL COMPETENCY, SUPPLY CHAIN CAPABILITY, AND ORGANIZATIONAL READINESS IN JAKARTA, TANGERANG, AND DEPOK - Verly, Christella Velita; Santosa, Wahyuningsih; Dewayana, Triwulandari Satitidjati (International Journal of Social Service and Research, 2024)
The application of digital technology in the food and beverage industry has benefits such as improving product quality, reducing energy consumption, and optimizing processes. This study aims to analyze the positive influence of Digital Technology on Operational Performance, Supply Chain Capabilities, and Digital Competition, as well as evaluate the impact of mediation by Digital Competency and moderation by Organizational Readiness in this context. Data was collected through a cross-sectional questionnaire. The results of regression analysis show that Digital Technology (TD) has a significant positive impact on Operationsional Performance (KOP) directly and through the mediation of supply chain capability (KRP), digital competency (KD), and organizational readiness (KOG). The correlation between TD and KOP of 0.763 shows a strong positive relationship, indicating that the increase in the implementation of digital technologies is closely related to the improvement of digital competence. The managerial implications of this study emphasize that organizations must adopt a holistic approach to digital transformation, which includes the development of supply chains capabilities, employee digital competencies, and organization readiness.